2015
DOI: 10.1039/c5md00320b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of indole-derived allocolchicine congeners exhibiting pronounced anti-proliferative and apoptosis-inducing properties

Abstract: Basing on the natural antimitotic agent allocolchicine as a lead structure, a series of novel indole-based allocolchicine congeners was synthesized and assessed in vitro for cytostatic properties. Several compounds exhibited potent antiproliferative and apoptosis-inducing activity towards lymphoma cells along with low unspecific cytotoxicity. The observed activity is supposed to result from the inhibition of microtubule assembly, as indicated by the tubulin polymerisation assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In 2012, the first allocolchicinoids with a heterocyclic ring (D) condensed to ring C were reported by N. Sitnikov et al Starting from 3,4,5-trimethoxyphenylpropionic acid ( 176 ), these authors developed a total synthesis of the pyrrolo-allocolchicinoids 178 and 179 and also of the related structures 183 and 184 with a reversed orientation of the N -methyl-indole fragment (Scheme ).…”
Section: Ring C Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, the first allocolchicinoids with a heterocyclic ring (D) condensed to ring C were reported by N. Sitnikov et al Starting from 3,4,5-trimethoxyphenylpropionic acid ( 176 ), these authors developed a total synthesis of the pyrrolo-allocolchicinoids 178 and 179 and also of the related structures 183 and 184 with a reversed orientation of the N -methyl-indole fragment (Scheme ).…”
Section: Ring C Modificationsmentioning
confidence: 99%
“…As a remarkable outcome of this study, alcohols and ketones of type 178 and 179 were found to exhibit strong antiproliferative and apoptosis-inducing activity against Burkitt’s lymphoma cells (BJAB) , in the nano- and subnanomolar concentration range, while showing only a relatively low nonspecific cytotoxicity.…”
Section: Ring C Modificationsmentioning
confidence: 99%
“…Only a few compounds were able to induce apoptosis in the measured concentrations up to 50 µM (see Table 2 ). Dihydroxyquingdainone ( 2g ) turned out to be the most promising compound, so we further characterised its effects in malignant cells; it has an AC 50 of 7.5 μM, which is the concentration of compounds able to induce apoptosis in 50 percent of the Nalm-6 cells after 72 h of incubation [ 16 , 17 , 18 , 19 , 20 ]. The non-substituted original quingdainone does not induce apoptosis in concentrations up to 100 µM.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most promising structures related to colchicine is allocolchicine, where the tropolone ring is replaced with a phenylene moiety. It has been reported that allocolchicine binds to tubulin more strongly than colchicine itself with a better therapeutic index. , …”
mentioning
confidence: 99%
“…It has been reported that allocolchicine binds to tubulin more strongly than colchicine itself with a better therapeutic index. 14,15 From a thorough SAR study of colchicine, it was found that the acetamide moiety can be replaced by other substituents without affecting the activity. 16 On the other hand, it is known that 1,2,3-triazoles are among the most common amide bond isosteres, where the lone pair of N-3 acts as a hydrogen-bond acceptor and the C−H replaces a hydrogen-bond donor.…”
mentioning
confidence: 99%